GROUND-SPACE METHODS FOR FORECASTING DEEP OIL-PERSPECTIVE HORIZONS - Sh. Zhantayev, Zh.; Fremd, A.G.; Iskakov, B.A. (Academic Scientific Journal of Computer Science, 2020)
The search for hydrocarbon deposits is a multifactorial task, which at present cannot be successfully solved on the basis of data from only one method. And for its solution, as a rule, a set of data is obtained, obtained both by ground means and remote, providing an objective picture of the structure of the sedimentary cover based on high information density without significant time and financial costs The paper considers modern methodological approaches used in the practice of prospecting for oil and gas, which give an objective idea of the criteria on the basis of which a geostructural image of a section of the geological environment is created. The resulting complex of terrestrial and remote data is aimed at clarifying the structure of the zones of possible oil and gas accumulation and identifying the most promising hydrocarbon traps within them. The main attention is paid to the identification of local structures of various types and discontinuous disturbances. It is the structural aspect, that is, the identification of discontinuous faults of various ranks and the determination of their parameters – strike, direction of fall and kinematics – that is most significant for determining the directions and choosing the methodology for oil and gas prospecting works in each specific area. The use of thermal range images with the construction of maps of surface temperatures and thermal anomalies based on them, taking into account the influence of the atmosphere, weather conditions, and geological features of the region under study, makes it possible to more efficiently identify productive structures and the most active faults at the present stage. Isolation of such objects makes it possible to concentrate on them seismic exploration and drilling, and thereby reduce the cost and significantly increase the reliability of forecasting and search operations carried out by traditional methods (geology, geophysics, geochemistry). Among them, in particular, is deep seismic exploration using the common depth point method, which allows to identify migration channels and fluid supports - structural elements that indicate the possible productivity of certain horizons. Nevertheless, despite the leading role of seismic exploration, interpretation of its data at great depths should be approached with some caution due to the high percentage of “dry” wells and the high cost of drilling itself. .Along with the existing ones, it is proposed and justified the use of the method of parametric 3D modeling of a geological section, which allows creating a visual spatial image of the distribution of oil prospective horizons. The method is verified on data from known deposits and showed good convergence of results. The results obtained are of interest to subsoil users and organizations planning to search for deposits in oilspitting regions.